How does the landscape uniformity in different forest landscapes affect the visual behavior and preference evaluation intention of participants—a case study of forest landscape in northern China (Liaoning) - Gao, Yu; Sun, Xiaomei; Zhang, Zhi; Zhang, Weikang; Meng, Huan; Zhang, Tong (Frontiers in Forests and Global Change, 2024)
Background: High-quality in-forest landscapes are very important when landscape designers and foresters are planning and managing forest landscape resources. Understanding people's visual-behavior toward in-forest landscapes plays an important role in creating high-quality in-forest landscape.Methods: People's visual information about in-forest landscapes with different landscape uniformity (IFLDLU) was visualized and digitized by eye-tracking technology and virtual reality method of picture, and the data were statistically analyzed by MANOVA, one-way ANOVA, Spearman's rho correlation analysis and linear regression in SPSS.Purpose: To discuss the influence of landscape uniformity on people's visual behavior, satisfaction preference and re-viewing intention, and to reveal the main reasons for the spatial cognitive characteristics of in-forest scenes that arouse their visual-attention and re-viewing intention.Main results: 1) The landscape uniformity of the in-forest landscape (IFL) affects people's observation mode; 2) People's visual attention differs across in-forest landscape uniformity, as mainly reflected in visual span and pupil diameter; 3) Overall, people prefer a cluster distribution of in-forest landscapes, for which they have higher re-viewing intentions; 4) Spatial cognitive characteristics that arouse participants' visual-behavior, satisfaction preference and re-viewing intention vary with the landscape uniformity of in-forest landscapes. Among them, many spatial cognitive characteristics should be optimized in random distribution for IFL, arousing higher satisfaction preference and re-viewing intention.Therefore, when planning, design and managing in-forest landscapes, we suggest that spatial cognitive characteristics should be improved and optimized based on the landscape uniformity of the IFL to arouse participants' positive visual-attention, enhance their place identity, make them "reluctant to bid farewell", and further arouse their place attachment.